2019
DOI: 10.1021/acsami.9b14415
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Microstructure and Rheology of Iridium Oxide Catalyst Inks for Low-Temperature Polymer Electrolyte Membrane Water Electrolyzers

Abstract: We present an investigation of the structure and rheological behavior of catalyst inks for low-temperature polymer electrolyte membrane water electrolyzers. The ink consists of iridium oxide (IrO 2 ) catalyst particles and a Nafion ionomer dispersed in a mixture of 1-propanol and water. The effects of ionomer concentration and catalyst concentration on the microstructure of the catalyst ink were studied. Studies on dilute inks (0.1 wt % IrO 2 ) using zeta potential and dynamic light scattering measurements ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 64 publications
2
31
0
Order By: Relevance
“…An I/C of ∼0.35, where the maximum stability of the catalyst in the inks was observed for all DM H 2 O % with 5 wt % catalyst concentrations, is a guideline for optimizing I/C in the inks with different catalyst concentrations. The particle agglomeration degree varies with the particle concentration (generally increases with the concentration); thus, the minimum I/C that maximizes catalyst stability may be expected to be higher or lower than 0.35 I/C depending on the catalyst concentration relative to 5 wt %.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An I/C of ∼0.35, where the maximum stability of the catalyst in the inks was observed for all DM H 2 O % with 5 wt % catalyst concentrations, is a guideline for optimizing I/C in the inks with different catalyst concentrations. The particle agglomeration degree varies with the particle concentration (generally increases with the concentration); thus, the minimum I/C that maximizes catalyst stability may be expected to be higher or lower than 0.35 I/C depending on the catalyst concentration relative to 5 wt %.…”
Section: Resultsmentioning
confidence: 99%
“…From extensive research on PGM CLs, many studies have demonstrated that the ink microstructure is dependent on the particle surface chemistry and formulation parameters such as DM composition and ionomer concentration. Catalyst inks are generally found to be agglomerated in the absence of an ionomer . The addition of an ionomer was found to reduce the agglomerated structure (i.e., stabilize the particles against agglomeration) of most catalyst/carbon inks (Pt-Vulcan, iridium oxide, Vulcan, high-surface area carbon), with an exception of Pt on high surface carbon. , Beyond the catalyst and ionomer, the DM type and composition (i.e., water/alcohol ratio) have also been found to affect the structure, performance, and stability of the resulting electrode. ,, …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure B, in the low-frequency region, G ′ < G ″ represented the viscous fluid behavior. With the content of synthesized Au increasing, the difference between G ′ and G ″ was reduced, demonstrating the occurrence of the aggregation and interwinding of cellulose chains in the solutions . With the rise of the angular frequency, both G ′ and G ″ increased and intersected with each other at a certain frequency, demonstrating that the gelation occurred.…”
Section: Results and Discussionmentioning
confidence: 95%
“…With the content of synthesized Au increasing, the difference between G′ and G″ was reduced, demonstrating the occurrence of the aggregation and interwinding of cellulose chains in the solutions. 40 With the rise of the angular frequency, both G′ and G″ increased and intersected with each other at a certain frequency, demonstrating that the gelation occurred. Subsequently, the frequency continued to increase, G′ > G″, by complying with the elastic behavior.…”
Section: ■ Experimental Sectionmentioning
confidence: 90%